2017
DOI: 10.1073/pnas.1615970114
|View full text |Cite
|
Sign up to set email alerts
|

Trio-based exome sequencing arrests de novo mutations in early-onset high myopia

Abstract: The etiology of the highly myopic condition has been unclear for decades. We investigated the genetic contributions to early-onset high myopia (EOHM), which is defined as having a refraction of less than or equal to −6 diopters before the age of 6, when children are less likely to be exposed to high educational pressures. Trios (two nonmyopic parents and one child) were examined to uncover pathogenic mutations using whole-exome sequencing. We identified parent-transmitted biallelic mutations or de novo mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 63 publications
1
73
1
Order By: Relevance
“…In this study, we identified a nonsense mutation (c.562C>T, p.R188*) in CEP250 in a consanguineous family with nonsyndromic RP by whole‐exome sequencing, which has been highly efficient in uncovering genetic defects (Jin et al, , , ). To further elucidate the functional relevance of the human CEP250 mutation, we generated knockin (KI) mouse models to investigate the roles of Cep250 in the retina in vivo .…”
mentioning
confidence: 99%
“…In this study, we identified a nonsense mutation (c.562C>T, p.R188*) in CEP250 in a consanguineous family with nonsyndromic RP by whole‐exome sequencing, which has been highly efficient in uncovering genetic defects (Jin et al, , , ). To further elucidate the functional relevance of the human CEP250 mutation, we generated knockin (KI) mouse models to investigate the roles of Cep250 in the retina in vivo .…”
mentioning
confidence: 99%
“…Epidemiological studies show that gout incidence increases with age until the age of 70 years and that onset before the age of 40 years is unusual [40,41]. A few studies have demonstrated that complex disease with earlyonset age could be caused by monogenic inheritance of mutated genes [42][43][44]. erefore, aiming to investigate potential causal gene in this pedigree, we used WES which has proven to be highly robust and efficient in the identification of disease-causing genes in monogenic conditions or complex disorders [45].…”
Section: Discussionmentioning
confidence: 99%
“…EoHM, defined as a high myopia onset before school age, is considered to be predominantly determined by genetic factors with minimal environmental effects. Mutations in at least 13 genes have been reported to cause eoHM, including ZNF644 (OMIM 614159), 8 SCO2 (OMIM 604272), 9 LRPAP1 (OMIM 104225), 10 SLC39A5 (OMIM 608730), 11 P4HA2 (OMIM 600608), 12 LEPREL (OMIM 610341), 13 ARR3 (OMIM 301770), 14 OPN1LW , 15 LOXL3 , 16 BSG , 17 CPSF1 , 18 NDUFAF7 , 19 and TNFRSF21 20 . However, mutations in these genes may only explain a small portion of patients with eoHM 21,22,23 .…”
Section: Introductionmentioning
confidence: 99%